BELAJA: ANALYSIS OF PRONUNCIATION REALIZATION OF IFL LEARNERS IN VICTORIA, AUSTRALIA - Arti Mustikaning Ati; Nuny Sulistiany Idris; Mochamad Whilky Rizkyanfi (RADJA PUBLIKA, 2026)
Pronunciation is a small part of the language skills that ILF (Indonesian as a Foreign Language) students should master. In IFL learning in Australia, communication skills are one of the elements in their newest curriculum. Correct pronunciation can be the key to a successful communication, but referring to previous research, pronunciation has not received much attention. This research was carried out to see realization of Indonesian pronunciation in the field by referring to articulatory phonetics theory. This qualitative descriptive research obtained its data from a secondary school in Victoria, Australia. The results show diversity such as inconsistencies in pronunciation, production of consonants with different articulators, the appearance of two sounds in one phoneme, and the loss of consonant sounds that should be pronounced.